(untitled) (Research, Society and Development, 2020)
Pinus taeda is cultivated in different regions of the world under different climatic conditions. The research was carried out aimed to evaluate the influence of climatic variables on the radial increment of growth rings in Pinus taeda L. trees. The evaluations were carried out on trees grown in Guarapuava, southern central region of Paraná state, Brazil. The half-yearly increments of growth rings were measured separately in autumn and spring. Nine climatic variables were considered and used factorial analysis to identify possible influences on the development of growth rings. Principal component analysis (PCA) was applied to evaluate increment data in semiannual periods and longitudinal statistical analysis to evaluate the increment of the rings over different years. It has been found that this species presents radial increment of growth rings benefited by higher temperature and rainfall indices in the growing season itself or in period immediately preceding.